The performance of china's state-owned commercial banks - Cai, Yun (2010)
The global financial crisis has worse hit the banking sector worldwide, in particular in the U.S. and Europe. However, according to the official reports of Chinese commercial banks, there was limited influence of the financial crisis on them. The Chinese banking sector has been continuously stable in developing in terms of risk defence and asset quality.